If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2m + 34 + -7(m + -3) = 8m + -1(5m + -7) + -6m + 6 Reorder the terms: -2m + 34 + -7(-3 + m) = 8m + -1(5m + -7) + -6m + 6 -2m + 34 + (-3 * -7 + m * -7) = 8m + -1(5m + -7) + -6m + 6 -2m + 34 + (21 + -7m) = 8m + -1(5m + -7) + -6m + 6 Reorder the terms: 34 + 21 + -2m + -7m = 8m + -1(5m + -7) + -6m + 6 Combine like terms: 34 + 21 = 55 55 + -2m + -7m = 8m + -1(5m + -7) + -6m + 6 Combine like terms: -2m + -7m = -9m 55 + -9m = 8m + -1(5m + -7) + -6m + 6 Reorder the terms: 55 + -9m = 8m + -1(-7 + 5m) + -6m + 6 55 + -9m = 8m + (-7 * -1 + 5m * -1) + -6m + 6 55 + -9m = 8m + (7 + -5m) + -6m + 6 Reorder the terms: 55 + -9m = 7 + 6 + 8m + -5m + -6m Combine like terms: 7 + 6 = 13 55 + -9m = 13 + 8m + -5m + -6m Combine like terms: 8m + -5m = 3m 55 + -9m = 13 + 3m + -6m Combine like terms: 3m + -6m = -3m 55 + -9m = 13 + -3m Solving 55 + -9m = 13 + -3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '3m' to each side of the equation. 55 + -9m + 3m = 13 + -3m + 3m Combine like terms: -9m + 3m = -6m 55 + -6m = 13 + -3m + 3m Combine like terms: -3m + 3m = 0 55 + -6m = 13 + 0 55 + -6m = 13 Add '-55' to each side of the equation. 55 + -55 + -6m = 13 + -55 Combine like terms: 55 + -55 = 0 0 + -6m = 13 + -55 -6m = 13 + -55 Combine like terms: 13 + -55 = -42 -6m = -42 Divide each side by '-6'. m = 7 Simplifying m = 7
| 60r+40s-100t= | | 14-7x=41-28x | | 4x=5x+2 | | 21p-49q-7= | | 85-5x=9x+19 | | y=(-143.3*81)+(1823.3*9)+6820 | | 2(x-6)=3x(-218) | | 12p-30q+36= | | 2*3.14*r=7.51 | | 7x-9x+6=-4x+6 | | 2a+6b+18c= | | 4/9(18w-36)-2/9(9w/2-9)=0 | | 5(x-1)=3(x+9) | | 32r-80z= | | 30m-120= | | s-15=-33 | | 24v+32w= | | 9p+21= | | 3x+2+5x-5=25 | | 6x+2y+6=0 | | 12x+8=10x+40 | | 10x^3+8x^2+2x=0 | | 9x+6-10x-25=30 | | 12n+2=4n+3 | | -3x+4=(-2)x+(-19) | | 4f-24g= | | 4+12/x=7 | | 12n+5=4n+6 | | -27-3x=6x+24 | | -81-9x=21+8x | | 10r-15s= | | 12n+3=4n-6 |